Individualization of basketball players (girls) coordination preparation at the stage of preparation for the highest achievements - Boichuk, R.; Iermakov, S.; Kovtsun, V.; Pasichnyk, V.; Melnyk, V.; Lazarenko, M.; Troyanovska, M. (Journal of Physical Education and Sport, 2018)
Aim: to substantiate expediency and effectiveness of individualization of the process of basketball players (girls) coordination preparation at the stage of preparation for the highest achievements. Material: 12 basketball players at the age of 17-19 years old participated in the study. Results: relevance of the introduction of individualization into the training process, its principles and implementation directions were revealed. It was proved that individualization increases the rationality of using the athletes` functional reserves and prevents the early end of a career. Structure of coordination preparedness of basketball players (girls) at the age of 17-19 years was determined, in which four expressed factors were revealed based on the factor analysis: rapid reconstruction of motor actions, kinesthetic differentiation, complex reaction, spatial orientation. Algorithm of determination of coordination abilities individual features in the structure of basketball players (girls) coordination preparation at the stage of preparation for the highest achievements is presented. Stages of determination of the individual factor structure of the athlete coordination preparation are shown. It is noted that, the crucial point is to provide conditions in which the period of maximum athlete's inclination to achieve the highest results coincides with the period of the most intense and complex coordination training loads at the stage of preparation for higher achievements. Conclusions: Basketball players (girls) training at the stage of preparation for higher achievements is a complex process where much attention should be paid to their individual abilities. Correction of the training process shall involve the development of those functions of the athlete`s body, which are the most expressed genetically and which are needed for the chosen sport. Technical preparedness of basketball players (girls) is determined by the level of various coordination abilities manifestation. In relation to the strategy of training the coordination abilities in basketball players (girls) in adolescence, it is necessary to know the sensitive periods for the development of these abilities, as well as age, gender and individual peculiarities of their formation.